Transformasi Digitalisasi Pajak Dalam Mendorong Kemandirian Fiskal Dan Pembangunan Ekonomi Nasional - Hulu, Ardiaman (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the impact of implementing a digital tax administration system on state revenue and public spending efficiency. Using descriptive qualitative methods, the study found that digitalization reduces the tax gap and increases the tax ratio. The results indicate that increasing fiscal independence through digitalization directly accelerates the financing of infrastructure development and public services.